Problematika Lingkungan Terhadap Regulasi Food Estate Sebagai Program Strategis Nasional di Desa Gunung Mas & Pulang Pisau Kalimantan Tengah: Environmental Problems with Food Estate Regulations as a National Strategic Program in Gunung Mas & Pulang Pisau Villages, Central Kalimantan - Baringbing, Mevitama Shindi (Fakultas Hukum Universitas Negeri Semarang, 2021)
Food Estate is part of the National Economic Recovery (PEN) program which aims to anticipate the food crisis in Indonesia due to the Covid-19 pandemic. The program is supported by the Job Creation Law which mandates ministers/heads of institutions, governors and regents/mayors to provide permits and non-permits required in the implementation of National Strategic Projects. One of the National Strategy Projects launched in 2020 is in the villages of Gunung Mas and Pulang Pisau, Central Kalimantan. Food Estate is expected to be able to combat the global food crisis in Indonesia. The Food Estate program is implemented on an area of 148,000 hectares, using the concept of food security and security. The research method used is a qualitative legal method. The results of this study found that the land clearing process caused various negative impacts felt by the customary law communities of Gunung Mas and Pulang Pisau Villages, the company used local labor with low wages, the selling value of smallholder agriculture was low. Therefore, food estates must be identified based on chronology, causal factors, impacts and resistance. The results in this paper will describe the negative impact of food estate on the environment and consider food estate as a national food security program, especially in facing future challenges.